Mental Fundamentals Role in Islamic Studies: Fundamental and Comparative Study - Charmand, Mohamad Mostafa (Journal of Islamic Sciences, 2024)
This is an original study of the concept of reason in Islam and highlights whether it has a role compared to those who took care of this concept among scholars. It adopted the method of analysis, rooting, and comparison, relying on the mothers of sources in this regard, to show through the study the mechanism of the work of the mind in legal science, especially in the sciences of the principles of religion and the principles of jurisprudence, which are the two sciences that are concerned with the Islamic scientific method. The study also aims to show the place of reason in reasoning and the extent of its authority in legislation, seeking accuracy and objectivity. The purpose of this study is to get out of the traditional cloak - texts - in which the legal science is marked so that the people of knowledge and its students work their minds in it, so that they complete what their ancestors began to store and enrich understanding, by reconsidering what was placed in their hands of the Islamic heritage, and knowing that it is advanced and has the characteristic of genius, and not reactionary or rigid.
Keywords: Mental fundamentals; Islamic Studies; mental evidence